2000
DOI: 10.2337/diabetes.49.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of albuminuria by aminoguanidine or ramipril in streptozotocin-induced diabetic rats is associated with the normalization of glomerular protein kinase C.

Abstract: This study examined whether the prevention of diabetes-related albuminuria by aminoguanidine (AG) or ramipril (RAM) may be mediated by a common postglomerular basement membrane renal intracellular mechanism involving protein kinase C (PKC). The renal handling of albumin was examined over 24 weeks in control and streptozotocin (STZ)-induced diabetic rats. A radioimmunoassay (RIA) that measures intact albumin, and intravenously injected tritium-labeled rat serum albumin, was used to assess the proportion of inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 35 publications
5
71
0
2
Order By: Relevance
“…Furthermore, a separate study in experimental diabetes has demonstrated no effect of aminoguanidine on PKC activity in the context of reduced AGEs (27), thereby confirming our current results. Other studies, however, have shown that treatment with aminoguanidine attenuates increases in PKC activity after 24 weeks of diabetes in glomeruli (8), retina, and mesenteric artery (28), although specific PKC isoforms were not addressed in that study. It appears likely that some of the differences seen in that study relate to the lack of examination of nonglomerular sources of PKC, such as tubules, which in this and previous studies have been shown to be major sites of expression and phosphorylation of various PKC isoforms (6,7).…”
Section: Diabetes Vol 53 November 2004mentioning
confidence: 75%
See 2 more Smart Citations
“…Furthermore, a separate study in experimental diabetes has demonstrated no effect of aminoguanidine on PKC activity in the context of reduced AGEs (27), thereby confirming our current results. Other studies, however, have shown that treatment with aminoguanidine attenuates increases in PKC activity after 24 weeks of diabetes in glomeruli (8), retina, and mesenteric artery (28), although specific PKC isoforms were not addressed in that study. It appears likely that some of the differences seen in that study relate to the lack of examination of nonglomerular sources of PKC, such as tubules, which in this and previous studies have been shown to be major sites of expression and phosphorylation of various PKC isoforms (6,7).…”
Section: Diabetes Vol 53 November 2004mentioning
confidence: 75%
“…Increases in PKC activity have been identified in vivo in renal glomeruli from streptozotocin-induced diabetic rats (8,9) and cells cultured under high-glucose conditions (10). Several studies have also reported attenuation of experimental diabetic nephropathy with the PKC-␤I inhibitor, LY333531 (11,12).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Modulation of PKC activity within the diabetic kidney has also been exhibited by various vitamin B derivatives (Babaei-Jadidi, Karachalias et al Hammes, Du et al 2003). Interestingly, both ACEi and aminoguanidine prevent diabetes associated increases in PKC  activation in renal glomeruli (Osicka, Yu et al 2000). The effects of aminoguanidine and ACEi on PKC  activity were also observed at other sites of vascular injury including the retina and mesenteric vascular bed (Osicka, Kiriazis et al 2001;Miyata, van Ypersele de Strihou et al 2002).…”
Section: Inhibition Of Protein Kinase C (Pkc) Activitymentioning
confidence: 76%
“…A diabetes és ennek kapcsán a magas vércukorszint indukálta proteinkináz-C aktivitásának fokozódása állatkísérletes adatok alapján központi szerepet tölt be a vascularis károsodások kialakulásában. Ugyanígy állatkísérletes adatok támaszt-ják alá, hogy ramiprillel csökkenteni lehet a diabetes kiváltotta proteinkináz-C-aktivitás fokozódását nemcsak a glomerulusokban, hanem a mesenterialis erekben és a retinában is [36,37]. Az Ang II által stimulált vascularis endothelialis növekedési faktor gátlása ramiprillel a retinavédő hatás egyik lehetséges magyarázata [38].…”
Section: áLlatkísérletekunclassified